2005
DOI: 10.1093/nar/gki584
|View full text |Cite
|
Sign up to set email alerts
|

HP1 modulates the transcription of cell-cycle regulators in Drosophila melanogaster

Abstract: Heterochromatin protein 1 (HP1) was originally described as a non-histone chromosomal protein and is required for transcriptional gene silencing and the formation of heterochromatin. Although it is localized primarily at pericentric heterochromatin, a scattered distribution over a large number of euchromatic loci is also evident. Here, we provide evidence that Drosophila HP1 is essential for the maintenance of active transcription of euchromatic genes functionally involved in cell-cycle progression, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 53 publications
4
80
1
Order By: Relevance
“…1360 is a repetitive sequence found most abundantly in constitutive heterochromatin regions of all Drosophila chromosomes and is believed to be essential for initiating heterochromatin formation 15,16 . Enrichment of HP1 binding to 1360 sequences has been detected previously by ChIP 17 . We found that association of HP1 with 1360 was significantly reduced following stat92E RNAi knockdown (Fig.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…1360 is a repetitive sequence found most abundantly in constitutive heterochromatin regions of all Drosophila chromosomes and is believed to be essential for initiating heterochromatin formation 15,16 . Enrichment of HP1 binding to 1360 sequences has been detected previously by ChIP 17 . We found that association of HP1 with 1360 was significantly reduced following stat92E RNAi knockdown (Fig.…”
supporting
confidence: 52%
“…Oligonucleotides used to amplify the 1360 transposon (forward: TGTATCGTTTTTAAAAAATTGTCAG; reverse: GTGGACCTGTAATATATGCTCT) were as described 17 . A 500-bp stat92E cDNA fragment was amplified by T7 promoter attached to PCR primers (forward: GAAT TAATACGACTCACTATAGGGAGACTTGCCCAAAACTACAGTTAC; reverse: GAATTAATACGACTCACTATAGGGAGACGACTGTGGGTGGATTGTT) and used for stat92E RNAi synthesis by in vitro transcription with the Fermentas T7 RNA transcription kit, according to the manufacturer's instruction.…”
Section: Cell Culture Oligonucleotides and Plasmidsmentioning
confidence: 99%
“…Chromatin precipitated by MYC-PIWI antibodies was recovered and the DNA was assayed by real-time PCR to quantify the association of MYC-PIWI with the F and 1360 elements-two transposable elements known to be preferentially bound by HP1a (De Lucia et al 2005). MYC-PIWI is enriched at F and 1360 elements 2.8-and 2.0-fold, respectively, over the housekeeping gene rpL32 (Fig.…”
Section: Piwi Colocalizes With Hp1a At Many Chromosomal Sitesmentioning
confidence: 99%
“…These include Drosophila HP1a, which is required for proper expression of most heterochromatic genes as well as a few euchromatic genes (Hearn et al 1991;Clegg et al 1998;Lu et al 2000;Piacentini et al 2003;Cryderman et al 2005;De Lucia et al 2005). Mammalian HP1␥ has also been shown to localize at active genes in a murine erythroid cell line (Vakoc et al 2005).…”
Section: The Contribution Of Hp1c To Gene Expressionmentioning
confidence: 99%
“…It is uncertain whether this general picture applies to all HP1 proteins and possible scenarios. Actually, Drosophila HP1a is known to play a more complex role(s) in the regulation of gene expression, as it is required for the expression of several heterochromatic genes (Hearn et al 1991;Clegg et al 1998;Lu et al 2000), and certain euchromatic genes (Cryderman et al 2005;De Lucia et al 2005). Moreover, Drosophila HP1a is recruited to developmentally regulated genes and heat-shock-induced puffs in an RNA-dependent manner , and in an erythroid cell line, murine HP1␥ was found associated to actively transcribed genes (Vakoc et al 2005).…”
mentioning
confidence: 99%